The Relationship Between the Duration of Gadget Use and Sleep Quality and Visual Acuity of Students at Panrita Husada Health College Bulukumba - Ani; Fatmawati; Nurlina (Comprehensive Health Care, 2025)
Gadget use can raise concerns regarding its impact on health and social life for adolescents. The results of interviews with 17 students of STIKES Panrita Husada Bulukumba with respondents who use gadgets showed that some respondents experienced sleep disorders, usually past 12 am to 3 am. In addition, respondents also said they usually felt eye fatigue, dry and itchy eyes, and blurred vision after using gadgets for too long. This study aims to determine the relationship between the duration of gadget use with sleep quality and visual acuity in students at STIKES Panrita Husada Bulukumba. The design used in this study was a quantitative descriptive correlational non-experimental with a cross-sectional approach. The number of samples in this study was 74 respondents using non-probability sampling techniques and purposive sampling methods. Data collection tools were questionnaires on the duration of gadget use, sleep quality, and visual acuity observation sheets. The results of the analysis using the Kolmogorov-Smirnov alternative Chi-square test on the relationship between the duration of gadget use with sleep quality and visual acuity obtained a significance value (p-value) of 0.000. Conclusions and Recommendations: There is a relationship between the duration of gadget use and sleep quality and visual acuity in students at STIKES Panrita Husada Bulukumba. Based on these results, it is recommended that students regulate the duration of gadget use, especially at night, to maintain sleep quality and eye health.